Socioeconomic inequalities affecting adult obesity in rural Bangladesh: evidence from the Bangladesh Integrated Household Survey - Ferdaush, Jannatul (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Applied Economics, 2019.